Preparation and properties of biobased autocatalytic polyols and their polyurethane foams. (January 2019) - Huo, Shuping; Jin, Can; Liu, Guifeng; Chen, Jian; Wu, Guomin; Kong, Zhenwu
Abstract: In the present work, we developed a green and more efficient method to prepare biobased polyurethane (PU) foams under catalyst-free condition. Firstly, novel organosilicon grafting cardanol-based autocatalytic polyols (SCAPs) with low viscosity were synthesized through the ring opening of cardanol glycidyl ether (CGE) and the hydrosilation of unsaturated alkyl chain with heptamethyltrisiloxane (HMTS). Subsequently, PU foams were synthesized by SCAPs in absence of catalyst. The structure and properties of the PU foams were evaluated and discussed. In addition, the thermal degradation mechanism of PU foams was investigated by using a thermogravimetric analysis instrument coupled with fourier transform infrared and mass spectrometer (TG-FTIR-MS). The results showed that the PU foams had high compression strength and thermo-stability. Graphical abstract: Highlights: Two novel bio-based autocatalytic polyols (SCAPs) with low viscosity were successfully synthesized from cardanol. Bio-based PU foams were further prepared from SCAPs in the absence of catalyst. The thermal degradation mechanism of obtained bio-based PU foams was systematically investigated by TG-FTIR-MS. The bio-based PU foams showed uniform closed-cell structure, and had high compression strength and thermostability.